Fenomena Covid-19 dalam Novel Burakku Shōman to Namonaki Machi no Satsujin Karya Keigo Higashino - Mandalle, Mesy Pramaseilla; Anwar, Fithyani (Vocational College of Diponegoro University, 2024)
This research focuses on the Covid-19 phenomenon depicted in the novel Burakku Shōman to Namonaki Machi No Satsujin by Keigo Higashino. This research uses the theory of literary sociology proposed by Alan Swingewood, who considers literary works as a tool to observe phenomena that occur in society at a certain period. The purpose of this study is to explain how the phenomenon of Covid-19 in the novel Burakku Shōman to Namonaki Machi no Satsujin is depicted and how it was a reality in Japanese society at that time. This research method uses a descriptive qualitative method. This research data comes from the novel and data in the form of facts that occurred in Japan. The results of this study show that the novel Burakku Shōman to Namonaki Machi no Satsujin can describe the reality of Covid-19 that occurred in Japan in the form of activity restrictions by the government, the implementation of health protocols, the slump in the economy and tourism, to the cancellation of major projects and the postponement of international events such as the 2020 Tokyo Olympics. Based on the analysis results, the novel is indeed the reality in Japanese society during the Covid-19 pandemic.